Diurnal variation in salivary progesterone in fertile Indian women. Issue 1 (January 2023) - Patil, Suvarna; Patil, Netaji; Bhat, Rohit; Hardikar-Bhat, Pallavi; Jadhav, Dnyaneshwar; Dervankar, Omkar; Joglekar, Charudatta; Shinde, Rohini; Desai, Shraddha; Chavan, Dhanashree; Pise, Megha; Nandoskar, Ajit
Abstract: Research question: Is there a diurnal variation in salivary progesterone levels during menstrual cycle among Indian women? Design: A longitudinal study was carried out to measure progesterone in saliva among small cross-sectional sample (n = 31) of fertile Indian women of reproductive age comprising young adults (18–25 years, n = 11), adults (26–38 years, n = 9) and middle aged (39–45 years, n = 11). Saliva samples were collected twice daily (morning and evening) across the entire menstrual cycle of 31 women. Results: Mean ages at enrolment and menarche were 30.6 years and 13.6 years respectively. Fifty-five percent of the women were married. The menstrual cycle range was 20–40 days. After controlling for age and menstrual cycle length, statistically significant diurnal variation in progesterone levels was observed across menstrual cycles with high levels in the morning. Conclusions: This is the first report on salivary progesterone in subjects with Indian ethnicity and could have clinical implications for designing point of care kits for menstrual cycle management, fertility and reproduction. Abstract : Progesterone plays a crucial role in reproductive health in regulating menstruation and supporting pregnancy. Knowledge of salivary progesterone patterns during the menstrual cycle can be used to develop point-of-care kits for reproductive health management.